2019
DOI: 10.1038/s41427-019-0184-0
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular vesicle (EV)-polyphenol nanoaggregates for microRNA-based cancer diagnosis

Abstract: Small extracellular vesicles (EVs), including exosomes, in body fluids have important applications in the noninvasive liquid biopsy-based diagnosis of cancer. Current EV-based diagnostic techniques still face practical challenges, such as inefficient EV isolation. Here, we report an efficient, resource-free pre-enrichment approach using (-)-epigallocatechin-3-gallate (EGCG), a polyphenolic biomolecule, to isolate and detect exosomal microRNAs (miRNAs) in human blood plasma samples. Our system comprises three s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…EVs adhered to EGCG to form EV aggregate bundles which were collected by filtration using a much lower pressure and shear force. They demonstrated that the EGCG-assisted filtration method isolated EVs more efficiently with higher purity compared with commercial EV isolation kits-ExoQuick Exosome Precipitation Solution (System Biosciences) and Total Exosome Isolation Reagent (Invitrogen) …”
Section: Isolation and Enrichment Of Evsmentioning
confidence: 99%
“…EVs adhered to EGCG to form EV aggregate bundles which were collected by filtration using a much lower pressure and shear force. They demonstrated that the EGCG-assisted filtration method isolated EVs more efficiently with higher purity compared with commercial EV isolation kits-ExoQuick Exosome Precipitation Solution (System Biosciences) and Total Exosome Isolation Reagent (Invitrogen) …”
Section: Isolation and Enrichment Of Evsmentioning
confidence: 99%
“…46), can give us information about genetic changes and gene expression profile of this cancer type (Ref. 45). EV signature is able to distinguish metastatic or non-metastatic breast cancer with high accuracy (~ 91%) (Ref.…”
Section: Extracellular Vesicles In Cancermentioning
confidence: 99%
“…Second, very low concentration of exosomes in serum samples (<10 9 vesicles/ml) is another issue (Ref. 45). Third, low levels of expressions for EV-related RNAs at early-stage cancer, detection of which at this stage is highly valuable (Ref.…”
Section: Extracellular Vesicles In Cancermentioning
confidence: 99%
See 2 more Smart Citations